Penerapan Aplikasi Daily Repot Departemen Qc PT. Talkindo Selaksa Anugrah Berbasis Website - Lusian Andrianto Andri; Sofa Sofiana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Currently the industrial world has entered the era of competition, as supporting production activities in a company or industry requires an information technology, not a few companies or industries have taken advantage of the development of this technology. Information technology is a valuable asset, especially for an industrial company in the food and beverage sector, as well as a system or mechanism for recording and processing daily work report data in a company as a system that can utilize technology as a tool for employees to do their work effectively. and efficient. PT. Talkindo Selaksa Anugrah especially in the QC department is one of the industrial companies in the food and beverage sector that does not yet have an information technology in terms of recording and processing daily work report data, where the system or mechanism for recording daily reports still uses forms and manual books. The method of implementing the system to design and build an application for this daily work report is using the Waterfall method, and using the PHP, HTML and CSS programming languages ​​with the MVC model and using the Codeigniter version 3 framework and the tools used are Sublime text 3 with the phpMyAdmin database and at this stage testing using Blackbox testing. So the application of this daily work report application can make it easier for employees to record and process daily work report data and can reduce the risk of loss and damage to daily work report data and can make it easier to search for the report data.